DAIRY CATTLE REPRODUCTIVE PERFORMANCE UNDER DIFFERENT PRODUCTION SYSTEM IN ETHIOPIA: NIGERIA’S BILATERAL TRADE RELATIONS WITH CHINA: AN ASSESSMENT, 2010 – 2019 - FEKATA, ABERA; MITIKU ESHETU (International Journal of Multidisciplinary Research and Studies, 2022)
Reproductive performance of dairy cattle in terms of age at first service (AFS), age at first calving (AFC), calving interval (CI), day open (DO), and a number of service preconceptions (NSPC) in the different production system in Ethiopia is reviewed. The reproductive performance parameter of dairy cattle like age at first serves (AFS), age at first calving (AFC), calving interval (CI), Day opens (DO), and the number of service preconceptions (NSPC) under different production system is quite different. Age at first calving (AFC) in pastoral and agro-pastoral and intensive dairy production systems were 43.5±1.5months and 33.2 months, respectively. Days open (DO) in pastoral and agro-pastoral, smallholder dairy production, and urban and dairy products for local cows were 141±7 days, 185±51.2days, and 199.8±11.60 days, respectively. 85 to 115days considered as optimum for a dairy herd, 116 to 130 days indicate slight problems, 131 to 145 days moderate problems. This, indicated that days open in the different production system is not within the normal range. Similarly, for cross dairy cows in an intensive dairy production system was157.8 days. The calving interval (CI) in pastoral and agro-pastoral, smallholder dairy production systems, urban and pre-urban for local cows were 14.63±10 months, 14.36± 1.03 months, and 22.17±0.79 months, respectively. Whereas urban and pre-urban and intensive dairy production for cross dairy cows were12.42±5.9 months, 15.820±.41months, and 14.56 months, respectively. NSPC for Horro x Jersey (1.8) and Horror (2.1) are not within the normal range, But for Borana (1.6), Fogera (1.28), Friesian x Zebu (1.56) were within the normal range. This difference might be due to poor management in terms of nutrition, health care, housing, heat detection, timely insemination, and breeding as well as environmental factors. It could be concluded that proper management in terms of nutrition, health care, housing, heat detection, and timely insemination would improve reproductive performance under different production systems. Besides this, to boost dairy cattle reproductive performance, intensification of dairy cattle production should be promoted in Ethiopia to meet the increasing demand for dairy products and to reduce imports of dairy commodities. Thus, all coordinated works of all concerned bodies should be in place to boost production and productivity and thereby enhance the livelihood of the dairy farmers.